2002
DOI: 10.1021/bi011676p
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Proton Abstracting Role of Glu-376 in Medium-Chain Acyl-CoA Dehydrogenase:  Influence of Glu-376→Gln Substitution on Ligand Binding and Catalysis

Abstract: The active site residue, Glu-376, of medium-chain acyl-CoA dehydrogenase (MCAD) has been known to abstract the alpha-proton from acyl-CoA substrates during the course of the reductive half-reaction. The site-specific mutation of Glu-376-->Gln(E376Q) slows down the octanoyl-CoA-dependent reductive half-reaction of the enzyme by about 5 orders of magnitude due to impairment in the proton-transfer step. To test whether the carboxyl group of Glu-376 exclusively serves as the active site base (for abstracting the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The light-excited minus dark-adapted difference spectrum of AppA156 (Figure 1B, inset) reveals negative features at 336, 352, 418, and 442 nm and positive peaks at 365, 387, 461, and 495 nm. Analogous spectral shifts in the visible region have been reported upon ligand and/or substrate binding to other flavoproteins (11)(12)(13)(14)(15)(16). Differing mechanisms have been proposed to account for these observed spectral profile variations, including π-π stacking ( 16), interactions of keto groups with the π-system of the flavin ring ( 14), and H-bonding at the O5 and N5 positions of the alloxazine ring (15).…”
Section: Resultsmentioning
confidence: 77%
“…The light-excited minus dark-adapted difference spectrum of AppA156 (Figure 1B, inset) reveals negative features at 336, 352, 418, and 442 nm and positive peaks at 365, 387, 461, and 495 nm. Analogous spectral shifts in the visible region have been reported upon ligand and/or substrate binding to other flavoproteins (11)(12)(13)(14)(15)(16). Differing mechanisms have been proposed to account for these observed spectral profile variations, including π-π stacking ( 16), interactions of keto groups with the π-system of the flavin ring ( 14), and H-bonding at the O5 and N5 positions of the alloxazine ring (15).…”
Section: Resultsmentioning
confidence: 77%
“…Mechanism of the PhotoconVersion. Factors inducing spectral changes of flavin-binding enzymes or sensory proteins can be grouped into four types: (i) hydrophobic property around the chromophore ( 29), (ii) H-bond between flavin and polar amino acid residues (10,18,19,(30)(31)(32), (iii) interaction between the molecular orbitals of the isoalloxazine ring of the flavin and the aromatic rings of amino acid residues (10), and (iv) (de-)protonation of the isoalloxazine ring of the flavin (11). Masuda et al reported a light-induced low-energy shift of C(2)dO and C(4)dO stretching vibrational modes of the isoalloxazine ring based on the FTIR spectroscopy of Slr1694 protein of Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…4C). Such a difference between the absorbance and CD spectra suggests a difference in the conformational shift of the reduced form of enzyme when it complexed with different substrates (25,27,36,52). This could be due to alterations in the conformation of the flavin isoalloxazine ring itself or in its position relative to an amino acid residue that can alter the flavin signal.…”
Section: Kinetic Properties Of Purified Wild Type and Mutantmentioning
confidence: 99%
“…Most frequently, the interaction between an ACD and various substrates is studied by monitoring characteristic absorbance changes at 450 and 560 nm following the addition of substrate to enzyme under anaerobic conditions. A decrease in absorbance at 450 nm is characteristic of the reduction of the essential FAD coenzyme, whereas an increase in absorbance at 560 nm is because of a new resonance signal related to the charge-transfer complex in the enzyme reaction (1,4,(25)(26)(27). In some situations, however, the observed changes at these wavelengths have been multiphasic, leading to difficulty in interpretation of the results.…”
mentioning
confidence: 99%